Collective turnover: An expanded meta-analytic exploration and comparison - Hancock, Julie I.; Allen, David G.; Soelberg, Craig (Human resource management review, 2017)
As evidenced by the publication of three meta-analyses in 2013, the importance of collective turnover is garnering increasing attention. Although each of these meta-analyses delivers a unique and significant impact to the HR literature, there remain opportunities to expand and build upon their contributions. In a comparison of the three extant meta-analyses, we found over 90 unique papers that were included in only one of each of the three studies, and >10 new studies published since 2013. We combined and expanded the existing meta-analyses, offering a comparison of results, as well as contributing to a greater understanding of the role of collective turnover. In the most comprehensive analysis to date, analyzing 2149 effect sizes from 159 studies across 150 articles, we find both support for and divergence from several previously examined relationships, as well as evidence of a curvilinear turnover-performance relationship and of the contagious influence of turnover. •Collective attitudes and perceptions, along with personnel changes, have the most impact on collective turnover.•Collective turnover has a negative relationship with overall organizational performance.•Managerial turnover strengthens the negative relationship among collective turnover and performance.•Evidence for contagion effects of turnover is demonstrated.•Evidence of curvilinearity is found.